ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN HIDROGEN SULFIDA PADA MASYARAKAT DI TPA SUMUR BATU, BANTAR GEBANG TAHUN 2023 - Gifta Alifa Annurullah (2023)
The accumulation and decomposition of organic waste at the landfill can cause air pollution because it produces Hydrogen Sulfide (H2S) pollutants. The gas can reduce air quality and cause health problems who living near the landfill. The gas can cause CNS injuries, irritation of the nose and throat, and lower respiratory tract to bronchitis. This study was to analyze the environmental health risks of H2S exposure to communities around Sumur Batu Landfill. The design of this research was Environmental Health Risk Analysis (EHRA). The study sample consisted of 83 people living within radius of less than 500 meters from the landfill who were selected by total sampling in May-June 2023. H2S were measured by impinger and then analyzed with a spectrophotometer at 4 different spots. The results showed that the average H2S concentration was 0.019 mg/m3. The average intake realtime and lifetime was 0.003 mg/kg/day and 0.004-0.009 mg/kg/day. Realtime risk level gets RQ>1 in 47 people. Lifetime risk level has an RQ>1 in 79 people for the next 30 years. It is concluded that the communities are at risk of health problems due to H2S, so risk management is needed.